1973
DOI: 10.1159/000136381
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacological Properties of Seclazone (7-chloro-3,3a-dihydro-2H, 9H-isoxazolo [3,2-b] [1,3] benzoxazin-9-one) A New Anti-Inflammatory Agent

Abstract: Seclazone possesses anti-inflammatory, analgesic and antipyretic properties. It effectively suppresses the development of adjuvant-induced polyarthritis in rats and the serum protein alterations associated with this condition. Seclazone also prevents phlogistic responses induced in rats by carrageenan. The anti-inflammatory effect of seclazone is not mediated by adrenocortical or pituitary stimulation since activity persists in adrenalectomized or hypophysectomized animals. Seclazone has an appreciable anti-br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1973
1973
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Berger et al (2,3) recently reported that seclazone (7-chloro-3,3a-dihydro-2H.9H-isoxazolo[3,2-b| [l,3|benzoxazin-9-one), a new heterocyclic compound with anti-inflammatory, analgesic, antipyretic and diuretic properties was highly effective in suppressing the development of both adjuvant-induced polyarthritis and the hind paw edema produced by various irritants in rats. In addition, seclazone had an appreciable antibradykinin activity in vitro (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Berger et al (2,3) recently reported that seclazone (7-chloro-3,3a-dihydro-2H.9H-isoxazolo[3,2-b| [l,3|benzoxazin-9-one), a new heterocyclic compound with anti-inflammatory, analgesic, antipyretic and diuretic properties was highly effective in suppressing the development of both adjuvant-induced polyarthritis and the hind paw edema produced by various irritants in rats. In addition, seclazone had an appreciable antibradykinin activity in vitro (3).…”
mentioning
confidence: 99%
“…In addition, seclazone had an appreciable antibradykinin activity in vitro (3). Metabolic studies in man, monkey, dog and rat (8) have shown that the compound under goes hydrolytic cleavage of the oxazine ring yielding 5-chlorosalicylic acid; this is the only hydrolysis product formed in the systemic circulation of rats after oral administration of the drug (9).…”
mentioning
confidence: 99%